Urban Agriculture: Experiences of Practitioners of Rooftop Gardening - K. Uma Rani; T.N. Reddy; S. Shah (Journal of Agricultural Extension Management, 2016)
A study on urban agriculture was conducted in selected urban areas of Hyderabad City. Fifty respondents who were practicing rooftop gardening were selected for the study. Vegetables, fruits and flowers were the commonly grown plants found in these rooftop gardens. It was found that majority of the practitioners were growing these plants o-rganically and they were able to meet their household requirements to a great extent except during the summer season. However, poor access to technical advice, non availability of services and quality inputs at reasonable price, potential leakages, lack of training and follow-up etc. were the major hindrances found in sustaining the practice